Rancangan Metode Manajemen Proyek Hibrida - Surya Gumilang, Anggit; Hardian, Bob; Raharjo, Teguh (Rifa'Institute, 2022)
PT Asuransi Simas Jiwa already has a standard or SOP for project management. However, the company growth, the dynamic business conditions, and expectations from management to produce products or services faster have made this SOP irrelevant. Some project management activities in the company that are not in accordance with the documented SOP make this condition worse. Project management in the company becomes ineffective and inefficient.Changes in the project management standards become an important thing. This research aims to produce an effective and efficient project management standard design for this company. This standard is expected to be able to regulate project management activities in this company with existing project management best practices. In addition, the proposed new standards must also meet the expectations of management.This research is a kind of qualitative research with design science research (DSR) research methods. This method was chosen because it can provide an opportunity for researchers to evaluate and improve each step of the research. In addition to the design and development phase, the researcher also adopted the agile transition practice selection framework. This research has two iterations. The first iteration produces a project management standard design that describes the real activities in this company. Meanwhile, the second iteration produces a draft of the project management standard that complies with project management best practices in accordance with the PMBOK seventh edition. The project management standard produced from the second iteration will be proposed to the company as a replacement for the current SOP.